03.02: Structural assessment of a column splice with opened slotted holes: Finger Connection. (13th September 2017) - Andrade, Pedro; Lagerqvist, Ove; Simões, Rui; Veljkovic, Milan
ABSTRACT: This paper introduces a novel joint based on a friction connection designed for column‐splices. The joint was developed within the scope of modular construction to improve the fast assembly of prefabricated frames and to accommodate eventual misalignments. Gaps at the connection are considered on the joint horizontal and vertical axis to accommodate misalignments whether they are rotations and/or displacements and so to allow for the easy fit of the columns. The efficiency of the joint resistance based on different connection gaps subjected to uniform compression is assessed.